2016
DOI: 10.1155/2016/6284595
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Infectious versus Sterile Perforated Corneal Ulcers after Therapeutic Penetrating Keratoplasty in the United States

Abstract: Purpose. To compare the long-term outcomes of infectious versus sterile perforated corneal ulcers after therapeutic penetrating keratoplasty in the United States. Methods. The charts of 45 consecutive eyes that underwent primary therapeutic penetrating keratoplasty for a perforated corneal ulcer at a single center were retrospectively reviewed. The perforated ulcers were classified as infectious or sterile and the underlying demographics, clinical features, and 36-month outcomes were compared among the two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…This result is comparable with other studies [ 4 , 18 ]. Groups of patients with extremely large corneoscleral grafts are usually small may be dependent on geographical and ethnic conditions (variability), and statistics may not be representative, which is also emphasized by other authors [ 2 , 4 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is comparable with other studies [ 4 , 18 ]. Groups of patients with extremely large corneoscleral grafts are usually small may be dependent on geographical and ethnic conditions (variability), and statistics may not be representative, which is also emphasized by other authors [ 2 , 4 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urgent penetrating keratoplasty (PK), total penetrating keratoplasty (TPK), and corneal or corneoscleral patch graft (CSPG) combination of surgical approaches or keratoprosthesis are usually reserved for progressive, end-stage corneal pathology or last-chance medical treatment [ 1 , 2 , 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal ulcers were considered central if located within 6 mm radius from central apex of cornea, and peripheral if any part of perforation was outside of this limit. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The associations were similar to those in previous studies, while preoperative time was rarely reported. These complications might account for the complicated surgery, with extreme difficulty in thoroughly excising infiltrated area, removing purulent membranes, and separating anterior synechiae 22,23. Hyphema was associated with surgical delay and the use of large graft, and was often due to the presence of refractory infection and multiple neovascularization 24.…”
Section: Discussionmentioning
confidence: 99%